PERENCANAAN BANGUNAN PENDIDIKAN BERTARAF INTERNATIONAL DI DEPOK - DIAN NUGRAHA (LPPM, 2013)
One of the efforts to create quality human is to improve the quality of education. Needs of the learners to get an international quality education occurs in primary education to higher education. Even now, many senior high school (SMA) which is developing itself into an international school or have international standards. With the application of international school expected students will eventually be able to compete and mempunnyai strong intellectual foundation. The purpose of this study to try to accommodate the demands of school that can develop in accordance with the times, which in this case is focused into the provision of physical infrastructure building to support the activities therein. Literature, field studies as well as studies banding. From this project is expected to create a school for the future. Both in terms of science and green building design. Science was created not to destroy nature, but to be able to work together with nature. Keyword: planning, space, building, education, international